STUDYING THE ELECTRICAL SYSTEM FOR THE NEEDS OF ELECTRICAL ENERGY AT THE PORT OF KIJING - Putra Halim, Nober Pratama; Arsyad, Muhammad Iqbal; Purworaharjo, Purworaharjo (Faculty of Engineering, Universitas Tanjungpura, 2023)
Electricity is one of the most important aspects of human life. It is required in various sectors. To maintain stability, electricity providers need to accurately forecast the demand for electricity. This research utilizes the Simple Linear Regression method with the assistance of Excel simulation. Based on the calculations, the analysis reveals the estimated power requirement for industrial load at Pelabuhan Kijing, particularly for the next 10 years, with a minimum of 4,053,685 Watts (4.053685 MVA) based on the predicted power consumption for each year, which experiences an average annual increase of 11.28%. The projected load for the year 2033 is estimated to be 5.802129 MVA. This study employs the one-way ANOVA analysis method to examine the data on the increase in the number of connected power loads in the industrial sector at Pelabuhan Kijing. The data collected from 2023 to 2033 indicates that there is no significant difference between the groups based on the ANOVA analysis. This conclusion is drawn from the ANOVA calculations, where the p-value is greater than the predetermined significance level. Thus, the predicted total load increase for the next 10 years suggests that there is no need to add transformer capacity since the existing capacity is sufficient. This research provides a better understanding of the growth trends in connected power loads and transformer capacity requirements at Pelabuhan Kijing within the specified time frame.